(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article investigates the body as textuality in the works of four Latin American artists: Ana Mendieta, Regina José Galindo, Lygia Clark and Priscila Rezende. The analysis is based on the theoretical reflections of Leda Maria Martins and Sueli Rolnik, which allow us to interpret the multiple layers of meaning of these productions. Furthermore, the study dialogues with the history of performance art, especially body art, supported by the studies of Roselee Goldberg. From these approaches, the centrality of feminine issues and the unique methods with which each artist treats the body in their artistic practices stand out.